Naskah Tentang Isra’ Mi’raj dalam Bentuk Nadoman - Mutakin Mutakin (Jurnal Lektur Keagamaan, 2013)
Islamic development in Indonesia, especially in Sunda archipelago, was not only affecting the development of language and literacy, but also in the form of poetic genre. Besides the form of poetry such as pupuh, tembang, etc. as well. Sundanese society also know types of poetry called as pupujian or syi’iran or nazhaman in Arabic (Sunda: nadoman). Nadoman has a consistent metric pattern, in which it consists of 4 syllables each arrays, with few arrays in an exception which has less or more than one syllable. The 24 syllables in one array, usually in the form of song genre, be beheaded with a pattern 4 | 4 | 4#4 | 4 | 4 (symbol #marking the middle side of array), transformed from the pattern bahr Rajaz Arabic poetry. The text of Isra Mi’raj containing the story of isra’ mi’raj has a significant social function as a medium of learning for Sunda-Islam society, especially Kuningan community where the manuscript was found. Through nadoman, the story of isra’mi’raj displayed in the form of “chanted poetry” that is easy to be remembered. Keywords: Ilmu ‘Arudl, Nadoman effective learning